Griddle and Chimney Conductivity in a Husk Furnace: An Influence of Oxygen Flow and Orifice Size - Irzaman, Irzaman; Rahmah Asri, Nurani Hanifan; Ridwan, Siskandar; Heriyanto, Syafutra; Renan, Prasta Jenie; Marina, Indriasari; Suharno, Suharno; Naila, Nur Alifa; Fara, Aulia Azzahra; Habibah, Assa'addah; Renny, Apriani Dwika Saputri (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
This research investigates the effect of oxygen flow valve orifice size on the thermal conductivity of a small-scale industrial husk furnace's pan and chimney. The researchers used a water boiling test to the thermal conductivity at varying valve hole sizes: 3627 cm, 3634 cm, 4334 cm, and 5034 cm. The pan, crucial for direct contact with cooking ingredients, and the chimney, responsible for fire flow during combustion, play vital roles in heating. The chimney, constructed of clay and zinc, exhibited thermal conductivity values ranging from 0.52 to 0.59 W m⁻¹ °C⁻¹. The highest chimney thermal conductivity was observed at the 50x34 cm valve hole size, attributed to a smaller temperature difference between the inner and outer chimney surfaces. The pan's average thermal conductivity ranged from 2.95 to 4.10 W m⁻¹ °C⁻¹, with the highest value recorded at 5034 cm orifice. This finding suggests a direct relationship between the valve hole size, heat transfer rate, and the pan's thermal conductivity. The research reveals the influence of oxygen flow on heat transfer within the husk furnace, providing valuable insights for optimizing its design and efficiency. While the chimney's thermal conductivity remained relatively stable across different orifice sizes, the pan's conductivity showed greater variation, potentially indicating inconsistent heat distribution. Further research with more precise temperature measurement techniques is recommended to refine these findings.